1964
DOI: 10.1111/j.1550-7408.1964.tb01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Excystation of Eimeria bovis and Other Species of Bovine Coccidia*

Abstract: SYNOPSIS. Mechanically released sporocyts of Eimeria bovis, E. ellipsoidalis and E. auburnensis readily excysted when incubated in a mixture of trypsin, steapsin, and bovine bile. Excystation of intact E. bovis, E. ellipsoidalis and E. auburnensis oocysts occurred after pretreatment at 37°C in aqueous 0.02 M cysteine hydrochloride under an atmosphere of CO2‐air or CO2‐N2, followed by incubation in an enzyme‐bile mixture. Nine % of E. bovis oocysts were activated after 6 hr of incubation at 37 C in a mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In most coccidian species examined to date, in vitro excystation may be elicited by exposure of oocysts to conditions simulating the gut environment of the host (i.e. host body temperature, COz, reducing conditions, trypsin, and bile salts) (6,7,9). Eimeriid coccidia, such as Eimeria and Zsospora, are characterized by oocysts possessing inner sporocysts, each of which contains infective sporozoites.…”
Section: Discussionmentioning
confidence: 99%
“…In most coccidian species examined to date, in vitro excystation may be elicited by exposure of oocysts to conditions simulating the gut environment of the host (i.e. host body temperature, COz, reducing conditions, trypsin, and bile salts) (6,7,9). Eimeriid coccidia, such as Eimeria and Zsospora, are characterized by oocysts possessing inner sporocysts, each of which contains infective sporozoites.…”
Section: Discussionmentioning
confidence: 99%
“…He stated that this action was enhanced by the addition of a reducing agent. Nyberg and Hammond (1964), Nyberg et al (1968), Hibbert and Hammond (1968), and Bunch and Nyberg (1970) each used reducing agents along with CO2 in their in vitro excystation experiments; however, the role of CO2 was emphasized with little importance attributed to the action of the reducing agent.…”
Section: Discussionmentioning
confidence: 96%
“…Previous investigations have shown that CO2 and a suitable reducing agent can change the oocyst wall permeability, allowing the entrance of trypsin and bile (Jackson, 1962;Nyberg and Hammond, 1964;Bunch and Nyberg, 1970). The mechanism of CO2 action, however, is not well understood.…”
mentioning
confidence: 97%
“…arloingi and E. intricata from sheep (Jackson, 1962;Bunch & Nyberg, 1970), E . bovis, E. auburnensis and E. ellipsoidalis from cattle (Hibbert & Hammond, 1968;Nyberg & Hammond, 1964) and for E . tenella, E. necatrix and E. acervulina from poultry (Hibbert & Hammond, 1968;Nyberg, Bauer & Knapp, 1968;Bunch & Nyberg, 1970).…”
Section: Activation Of Endoparasites 289mentioning
confidence: 99%
“…bovis (Fig. I) to stain more readily with toluidine blue (Nyberg & Hammond, 1964). Lotze & Leek (1960) concluded that the oocyst wall of three species of Eimeria from sheep (Table 2) must be conditioned by the primary stimulus, so that the activator(s) in the small intestine could rapidly penetrate to the sporozoites.…”
Section: Activation Of Endoparasites 289mentioning
confidence: 99%